Toxic work environment: the impact of toxic leadership and workplace bullying on employees’ innovative work behavior and affective commitment - Fadi Bou Reslan; Souad Hassanie; Orhan Uludag; Sirine BouKarroum; Nada Jabbour Al Maalouf (Cogent Business & Management)
Drawing on the conservation of resource theory and social exchange theory, this paper investigates the impact of toxic leadership and workplace bullying on healthcare workers’ innovative work behaviors and affective commitment. The hypothesized relationships were tested using time-lagged data and multiple sources collected from 257 nurses and 39 supervisors in private hospitals in Germany and analyzed via structural equation modeling. Our findings reveal that toxic leadership has a significant negative impact on nurses’ innovative work behavior (β = −0.47, p < 0.01) and affective commitment (β = −0.39, p < 0.01). Furthermore, workplace bullying has a significant negative effect on employees’ innovative work behavior (β = −0.46, p < 0.01) and affective commitment (β = −0.51, p < 0.01). Moreover, the dyadic results revealed that nurses’ self-ratings are consistent with the evaluations provided by their supervisors. This paper is one of its kind examining how a toxic workplace diminishes employees’ affective commitment and innovative behaviors in response to resource depletion and disruption of the social exchange relationship utilizing a dyadic approach. Several managerial implications were discussed to reduce workplace toxicity such as adopting continuous training on conflict management, providing leadership development programs, and integrating anonymous reporting systems highlighting the tools to evaluate the success of these initiatives.